Management in private and public sectors as an important element of the functioning of the organization - Artman, Monika; Boiko, Margarita; Buniak, Nadiia; Cherchуk, Larysa; Deineha, Inna; Fedoniuk, Anatolii; Gudz, Petro; Hulchak, Oleksandr; Jarosh, Piotr; Marceli, Ryszard Gęśla; Khomiuk, Nataliia; Kulyk, Mariia; et al. (Higher School of Social and Economic, 2024)
The presented materials have theoretical, and methodological value as well as didactic and practical significance, as they demonstrate the conditions and features of implementing effective management tools and methods to address current issues in enterprise, activity areas, and regional development. This monograph will be valuable and beneficial for enterprise managers, local government officials, researchers, and university students.
Keywords: management